An Empirical Test of a Model Proposed by Chambers. - McKeown, James C. (The Accounting Review, 1971)
Abstract One of the major criticisms of accountants in recent years has been their failure to present financial statements which have current relevance. Several individuals and groups have published theoretical descriptions of accounting systems based either partly or wholly on some form of current value. This, however, has not completely solved the problem since little or no work has been done to investigate the feasibility or practical implications of these models. There are several reasons for the lack of innovation aimed at improvement of the relevance of published financial statements. The public, investors, analysts and small creditors, do not have the direct power that management and large lenders have to demand more relevant statements. Corporate accountants have in large measure tended to concentrate on refining existing techniques rather than developing basic new methods of presenting information. For these reasons, the lead in determining the feasibility of the current-value-based models has fallen mainly to the academic accountant, who has a minimum of vested interest in maintaining the status quo and a maximum interest in improving statement presentation.